Meta-Analysis: Bullying's Effects on Anxiety and Depression in Adolescents - Amin Nur Hanida; Bhisma Murti; Didik Gunawan Tamtomo (Journal of Health Promotion and Behavior, 2025)
Background: Bullying is a major problem worldwide. Bullying itself is defined as a condition in the form of negative and repetitive behavior, carried out by a person or group of people, the treatment is carried out deliberately and intensely with the aim of hurting physically and mentally. This study aims to analyze and estimate the magnitude of the influence of bullying on anxiety and depression in adolescents. Subject and Method: The meta-analysis was performed according to the flow of the PRISMA diagram and the PICO model. P: Adolescents, I: Bullying, C: No bullying, O: Anxiety and depression. The search for articles in this study is through databases that include PubMed, Google Scholar, Science Direct and Scopus. With keywords including: "bullying" AND "anxiety" AND "depression" AND "adolescent". Full paper article with cross-sectional study, the subject of the study was adolescents, the measure of the relationship used was adjusted Odds Ratio,   the outcome of the study was anxiety and depression. Analysis was done with Revman 5.3 Results: There were 10 articles with cross-sectional designs from the United States, Africa, China, Saudi Arabia, Malaysia, and Australia with a total of 282,799 research samples. A meta-analysis of 10 cross-sectional studies concluded that adolescents who experienced bullying had a 1.98 times greater risk of anxiety than those without bullying (aOR = 1.98; CI 95%= 1.54 to 2.53; A meta-analysis of 8 cross-sectional studies concluded that adolescents who experienced bullying had a 1.85 times greater risk of depression compared to no bullying (aOR= 1.85; CI 95%= 1.37 to 2.50; p<0.001). Conclusion: Bullying increases the risk of anxiety and depression in adolescents